2021
DOI: 10.1111/bcp.14881
|View full text |Cite
|
Sign up to set email alerts
|

Nemonoxacin dosage adjustment in patients with severe renal impairment based on population pharmacokinetic and pharmacodynamic analysis

Abstract: Aims: To optimize the dosing regimen in patients with severe renal impairment based on population pharmacokinetic (PPK)/pharmacodynamic analysis. Methods:The pharmacokinetics and safety of nemonoxacin was evaluated in a single-dose, open-label, nonrandomized, parallel-group study after single oral dose of a 0.5-g nemonoxacin capsule in 10 patients with severe renal impairment and 10 healthy controls. Both blood and urine samples were collected within 72 hours after admission and determined the concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Two PK studies on nemofloxacin showed a higher incidence of AEs in patients with mild and moderate hepatic or renal impairment with a creatinine clearance of ≥50 ml/min compared with the healthy population. Yet, they showed good tolerability and safety profiles of oral single-dose 500 mg nemonoxacin (Table 4) (Xiaoyong et al, 2020;Li et al, 2021). Study drug-related AEs manifested as Q-T interval prolongation, T wave change, white blood cell count decrease, total bilirubin increase, and skin pruritus, all of which were mild and transient, and the patients recovered without any treatment.…”
Section: Patients With Renal or Hepatic Impairmentmentioning
confidence: 99%
“…Two PK studies on nemofloxacin showed a higher incidence of AEs in patients with mild and moderate hepatic or renal impairment with a creatinine clearance of ≥50 ml/min compared with the healthy population. Yet, they showed good tolerability and safety profiles of oral single-dose 500 mg nemonoxacin (Table 4) (Xiaoyong et al, 2020;Li et al, 2021). Study drug-related AEs manifested as Q-T interval prolongation, T wave change, white blood cell count decrease, total bilirubin increase, and skin pruritus, all of which were mild and transient, and the patients recovered without any treatment.…”
Section: Patients With Renal or Hepatic Impairmentmentioning
confidence: 99%